Comparison of Bone Mineral Density Between Veterans and Non-Veterans and Its Impact on Fracture Risk Assessment - Ya-Lien Deng; Chun-Sheng Hsu; Yi-Ming Chen; Shih-Yi Lin; Tse-Yu Chen; Chi-Ruei Li; Hsu-Tung Lee; Ying-Chia Wu (Medicina)
Background and Objectives: Osteoporosis poses significant health risks, especially among veterans, due to lifestyle factors. This study compares bone density and fracture risks between male veterans and non-veterans. Materials and Methods: We conducted a retrospective analysis of 1427 veterans from the Taichung Veterans General Hospital osteoporosis database (2010–2022), matched 1:1 by age and gender with non-veterans. Bone mineral density (BMD) was measured via dual-energy X-ray absorptiometry (DXA). Comorbidities, fracture sites, and mortality data were tracked. Conditional logistic regression was used to identify factors influencing fracture risk. Results: The study found that veterans have a higher fracture risk (univariable OR 1.24, multivariable OR 1.20, p < 0.001). Fracture victims were slightly younger in the veterans group (78.7 ± 10.0 years vs. 80.1 ± 9.2 years, p = 0.010), who also had better T-scores in the lumbar spine and left femoral neck. Veterans showed a higher post-fracture mortality rate (39.9% vs. 31.9%, p = 0.001) and a greater incidence of radial fractures (5.01% vs. 2.96%, p = 0.036). Importantly, veterans exhibited a trend toward more hip fractures compared with non-veterans (27.0% vs. 23.6%, p = 1.017), suggesting a potential difference despite not reaching statistical significance. Conclusions: In the present study, we found that veterans have higher rates of comorbidities, and higher mortality after a fracture event, highlighting the need for targeted medical interventions to address these differences. Further intervention to prevent avoidable fractures and the provision of adequate care for long-term osteoporosis management remain critical issues.